UPAYA PENINGKATAN KEPATUHAN TENAGA KESEHATAN DALAM RANGKA PENCEGAHAN DAN PENGENDALIAN INFEKSI (PPI) DI PUSKESMAS CANDIROTO KABUPATEN TEMANGGUNG - Junianto, Rohedy Kartiko; Priyastiwi, Priyastiwi; Subkhan, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The aim of this research is to find out why health workers' compliance in the context of Infection Prevention and Control (PPI) at the Candiroto Health Center, Temanggung Regency is still not optimal and to formulate efforts to increase health workers' compliance in the context of Infection Prevention and Control (PPI) at the Candiroto Health Center, Temanggung Regency. The research results stated that the compliance of health workers in the context of Infection Prevention and Control (PPI) at the Candiroto Community Health Center, Temanggung Regency is still not optimal in terms of monitoring the implementation of PPI activities, PPI education for employees and PPI education for visitors. Efforts to increase the compliance of Health workers in the context of Infection Prevention and Control (PPI) at the Candiroto Community Health Center, Temanggung Regency, are by: (1) Monitoring the implementation of Sterilization, Disposal of infectious waste, body fluids and blood, Disposal of sharp objects and needles, Hand hygiene and PPE Compliance ; (2) PPI education for employees in increasing compliance with SOPs relating to PPI, decontamination of medical equipment, waste management, linen management, employee health protection and cough etiquette; (3) PPI education for visitors to improve hand hygiene and cough etiquette.